Relationship between Proximate Characteristics and pH Value with Total Lactic Acid Bacteria in Etawa Goat Milk - Annisa Farma; Djong Hon Tjong; Endang Purwati; Anthoni Agustien; Annisa Khaira (Jurnal Biologi Tropis, 2026)
Etawa goat milk is a highly nutritious food source with strong potential to be developed as a functional food. Its nutritional components—such as protein, fat, and water content—along with the presence of lactic acid bacteria (LAB), contribute to its health benefits. This study aimed to analyze the proximate characteristics and pH value of Etawa goat milk and to evaluate their relationship with the total LAB count. Milk samples were collected from three locations in Padang City: Gunung Pangilun, Korong Gadang, and Padayo. Proximate analysis was conducted using standard methods from the Indonesian National Standardization Agency, while total LAB was determined using the Total Plate Count method on MRS Agar media. The results showed that moisture content ranged from 86.11–88.93%, protein content from 3.64–4.17%, fat content from 4.00–5.00%, and pH values from 6.70–7.00. The total LAB ranged from 30.66×10⁸ to 48.33×10⁸ CFU/mL, exceeding the minimum threshold required for probiotic sources. Samples with higher protein and fat content tended to have higher LAB counts. In addition, high moisture content and near-neutral pH supported microbial growth. Therefore, the proximate characteristics and pH value of Etawa goat milk are associated with LAB counts, indicating its potential as a natural probiotic source. The findings of this study provide scientific evidence for the utilization of Etawa goat milk as a natural probiotic product and may contribute to the development of dairy-based functional foods and community nutrition programs.